EFFECT OF FOLIAR SPRAY WITH ALPHA-TOCOPHEROL AND ORGANIC FERTILIZATION WITH MUSHROOM COMPOST ON GROWTH OF ASWAD DIALA FIG TRANSPLANTS: EFFECT OF FOLIAR SPRAY WITH ALPHA-TOCOPHEROL AND ORGANIC FERTILIZATION WITH MUSHROOM COMPOST ON GROWTH OF ASWAD DIALA FIG TRANSPLANTS (Iraqi Journal of Market Research and Consumer Protection, 2026)
This study was conducted at Research Station of College of Agricultural Engineering Sciences, University of Baghdad, during 2023 growing season to investigate the effect of alpha-tocopherol and levels of organic fertilization with spent mushroom compost (SMC) on some vegetative growth traits of two-year-old Aswad Diala fig transplants planted in 30 cm plastic pots. The experiment included spraying alpha-tocopherol at four concentrations (0, 100, 200, 300 mg L-1) and fertilizing transplants with three levels of spent mushroom compost (0, 1, 2 kg per transplants). The experiment was designed under a randomized complete block design with three replicates. The results showed significant increases in all studied traits. Spraying alpha-tocopherol at concentrations of 300 and 200 mg L-1 significantly exceeded the control in leaf elemental content (mg), chlorophyll a and b, dry weight, and leaf fresh weight. Meanwhile, transplants fertilized with spent mushroom compost at ratios of 3:1 and 2:1 excelled in mentioned traits.